ITKids Part I: Children's occupations and use of information and communication technologies - Ciccarelli, Marina; Straker, Leon; Mathiassen, S.; Pollock, Clare (IOS Press, 2011)
Objective: School children use information and communication technology (ICT) on a regular basis for a variety of purposes. The purpose of this study was to document how school children spend their time and the different types of ICT they use. Methods: Nine Australian primary school children were observed in their school and away-from-school environments during one school day to record their ICT usage, comparing self-report exposures with direct observations. Self-reported discomfort scores were obtained throughout the day.Results: Paper-based ICT (Old ICT) was mostly used for productive occupations at school, while electronic-based ICT (New ICT) was mostly used during leisure in away-from-school locations. Tasks involving no ICT (Non-ICT) accounted for the largest proportion of time in both locations during self-care, leisure and instrumental occupations. End-of-day self-reported time performing different occupations was consistent with data from independent observations. Self reported time using Old ICT and New ICT was marginally over-estimated, and time spent using Non-ICT was marginally under-estimated. Conclusion: The children in this study used a variety of ICT in the performance of daily occupations in their natural environments. New ICT use was primarily for leisure, but time spent was less than reported in other studies. Discomfort reports among the participants were low. Participants' self-reports of occupations performed and ICT use was reliable and could be useful as an exposure assessment metric.